Pengaruh Persepsi Harga dan Kualitas Pelayanan terhadap Keputusan Pembelian Jasa Wedding Organizer : Survei pada Konsumen Permata Wedding Organizer Tasikmalaya - Sopa Awaliyah (CV. Ulil Albab Corp, 2022)
This study aims to determine the effect of perceived price and service quality on purchasing decisions for wedding organizer services (a survey of consumers of Permata Wedding Organizer Tasikmalaya). The research method uses quantitative methods with a survey approach, surveys in this study were to consumers of Permata Wedding Organizer with a sample of 70 people. The data used are primary and secondary data. The data analysis technique used is Multiple Linear Regression Analysis using SPSS v.25 Software. The results showed that simultaneously Price Perception and Service Quality had a significant influence on Purchase Decisions. Partially price perception has a significant influence on purchasing decisions. Partially Quality of Service has a significant influence on Purchase Decisions.